Les réactions de la doctrine à la création du droit par les juges en droit administratif - Lemieux, Pierre (Les Cahiers de droit, 1980)
This paper surveys the outlook and statements of Quebec and Canadian legal scholars and judges on issues of administrative law. It attempts to determine whether scholarly writings merely describe the existing state of the law, or whether they play a creative role in pointing for the courts the way in which law should develop towards an ideal model. To this end, an assessment is first made of the creative power of judges when interpreting the law and of the reactions of scholars to this. Then, an attempt is made to show affinities between judges' and scholars' outlook in cases where an administrative decision conflicts with individual rights or liberties. The paper concludes that while most public law writing in Canada and Quebec usually reads as a restatement of current case law, recent works show an increasing tendency towards independent, critical legal thinking.